2015
DOI: 10.1093/ee/nvv055
|View full text |Cite
|
Sign up to set email alerts
|

Resource Allocation to Flight in an Outbreaking Forest Defoliator Malacosoma disstria

Abstract: Allocation of larval nutrients affects adult life history traits in insects. This study assessed the effect of moth age and wing loading on flight capacity in an outbreaking forest lepidopteran, Malacosoma disstria Hübner . Insects were collected from high and low density populations after larval feeding, and flight capacity was tested directly with flight mills and indirectly through the allometric relationship between wing area and body size. Insects from these same populations collected as eggs and fed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…There was, however, no effect of male moth body size on the proportion of released moths captured in sentinel female-baited traps. Flight capacity of male forest tent caterpillar moths is not influenced directly by wing loading but is limited by energy use (Evenden et al, 2015). As the field cage limited the dispersal distance of released moths in the current study, energy use is likely not a factor in male moth orientation to females within the cage.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…There was, however, no effect of male moth body size on the proportion of released moths captured in sentinel female-baited traps. Flight capacity of male forest tent caterpillar moths is not influenced directly by wing loading but is limited by energy use (Evenden et al, 2015). As the field cage limited the dispersal distance of released moths in the current study, energy use is likely not a factor in male moth orientation to females within the cage.…”
Section: Discussionmentioning
confidence: 69%
“…Male flight requirements to find females will likely vary with population density and by extension with availability of larval nutrition whereby less food may be available at higher densities. Recent research (Evenden et al, 2015) showed that flight capacity was not influenced by wing loading of male forest tent caterpillar moths collected from populations at different densities but energy use in flight increased with distance flown. At low population densities, males may have to fly considerable distances to encounter a receptive female (Elkinton and Cardé, 1980;Sanders, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…The extent and manifestation of these trade‐offs is largely species specific and is not well understood for many species (Colvin & Gatehouse, ; Zhang et al., ). Oogenesis and flight activities compete for energy reserves and extended flight can cause a decrease in fecundity and fertility, as observed for the diamondback moth, Plutella xylostella (L.) (Shirai, ), and the forest tent caterpillar, Malacosoma disstria (Hübner) (Evenden et al., ). In some species, syndromes of physiological characteristics (sensu Dingle, ) are observed through which the timing of reproduction and flight is coordinated (Dingle, ).…”
Section: Introductionmentioning
confidence: 92%
“…After 7-10 days, adults emerge, mate, and oviposit. Adults of both sexes are strong fliers, and can disperse up to 19 km a year (Evenden et al, 2015). When assisted by turbulent cold air masses, some have been reported to fly hundreds of kilometers (Brown, 1965;Fullard and Napoleone, 2001).…”
Section: Introductionmentioning
confidence: 99%